A research on College students’ Burnout in Mixed Online and Offline English Teaching Model - Wei, Haimei (International Journal of Education and Humanities, 2024)
Burnout is one of the most common emotions in foreign language learning. In the new era, mixed online and offline model of learning foreign languages has become a trend, but learning burnout still exists. Many scholars have investigated the burnout of foreign language teachers or students in traditional classroom teaching, but there is little research on online and offline blended teaching. Through questionnaire and interview, the present study uses the burnout rating scale to investigate mixed online and offline college English learning burnout of 60 college students of different genders, majors and grades. The results show that burnout is common in mixed foreign language teaching. The general burnout situation in online and offline teaching is not noticeable while certain specific syndromes are different. Foreign language learning burnout is related to gender, major and college English learning length. This study hopes to provide more thinking space for reducing foreign language learning burnout and improving students’ well-being